Impact of Protracted Displacement on Delay in the Diagnosis Associated with Treatment Outcomes: A Cross-Sectional Study in Internally Displaced Tuberculosis Patients of Pakistan - Farman Ullah Khan (MDPI AG, 2021)
Human displacement is on the rise globally, and the increase in the burden of tuberculosis (TB) is also attributed to migrations worldwide. A significant number of such displacements occur in regions with considerably higher areas of TB burden. Displacements may delay TB diagnosis and treatment, which will possibly lead to TB transmission among healthy individuals. In this study, we assessed the association of existing determinants after a protracted internal displacement of people with delay in TB diagnosis and treatment outcomes. A cross-sectional study was conducted on internally displaced TB patients (IDPs), registered at selected health facilities in three urban districts of Pakistan from March 2019 to February 2020. The univariate and multivariate logistic regression model was used to assess the delay in diagnosis and treatment outcomes. IDPs with delay in initiation of treatment beyond 30 days were at high possibility of unsuccessful TB treatment outcomes (adjusted odds ratio AOR, 2.60; 95% CI 1.06–6.40). Furthermore, the multivariate regression analysis showed a statistically significant association (p > 0.05) between TB patients who were aged 55 to 65 years (AOR, 2.66; 95% CI 1.00–7.07), female patients (AOR, 2.42; 95% CI 1.21–4.81), visited non-formal health provider (AOR, 8.81; 95% CI 3.99–19.46), self-medication (AOR, 2.72; 95 % CI 1.37–5.37), poor knowledge of TB (AOR, 11.39; 95% CI 3.31–39.1), and perceived stigma (AOR, 8.81; 95% CI 3.99–19.4). Prolonged delay in treatment was associated with unfavorable treatment outcomes among IDPs. Migrants and IDPs are more likely to experience an interruption in care due to overall exclusion from social and health care services. Therefore, it is imperative to understand the barriers to providing public health care services, particularly in preventing and treating TB.